Child-birth cosmovision - María Dolores López Gómez; Elena López Terol; Mar Pérez López; Josefa F. Such Boluda; Inmaculada Vidagany Escrig (Universidad de Alicante, 1999)
We have tried to capture knowledge, values and beliefs surrounding the phenomenon of child-birth. To be more precise, our aim has been to focus on the cosmovision surrounding the new-born human being, trying to link as much as possible the situation of child-birth with our performance as health professionals. Interviews have taken place among a population geographically close to our working field. In them, we have discovered beliefs, attitudes, somehow representative of the different ways in which, diverse cultures treat health care. Our feeling is that, if our education programmes for health in new-born babies are to prove effective, then we first have to be acquainted with the population's anthropological vision.